The raising of minimum alcohol prices in Saskatchewan, Canada: Impacts on consumption and implications for public health - Stockwell, Tim; Zhao, J.; Giesbrecht, N.; Macdonald, S.; Thomas, G.; Wettlaufer, A. (2012)
Objectives: We report impacts on alcohol consumption following new and increased minimum alcohol prices in Saskatchewan, Canada. Methods: We conducted autoregressive integrated moving average time series analyses of alcohol sales and price data from the Saskatchewan government alcohol monopoly for 26 periods before and 26 periods after the intervention. Results: A 10% increase in minimum prices significantly reduced consumption of beer by 10.06%, spirits by 5.87%, wine by 4.58%, and all beverages combined by 8.43%. Consumption of coolers decreased significantly by 13.2%, cocktails by 21.3%, and liqueurs by 5.3%. There were larger effects for purely off-premise sales (e.g., liquor stores) than for primarily on-premise sales (e.g., bars, restaurants). Consumption of higher strength beer and wine declined the most. A 10% increase in minimum price was associated with a 22.0% decrease in consumption of higher strength beer (> 6.5% alcohol/volume) versus 8.17% for lower strength beers. The neighboring province of Alberta showed no change in per capita alcohol consumption before and after the intervention. Conclusions: Minimum pricing is a promising strategy for reducing the public health burden associated with hazardous alcohol consumption. Pricing to reflect percentage alcohol content of drinks can shift consumption toward lower alcohol content beverage types.